Ecological and physiochemical effect of aquatic plants in eutrophication water - WU Yue-yan; WU Qiu-feng; CENG Hua-jun (浙江大学学报. 农业与生命科学版)
By cultivating four aquatic plants including Myriophyllum spicatum Linn., Hydrocotyle vulgaris Linn., Jussiaea repens Linn. and Nymphoides peltatum (Gmel.) O. Kuntze. in a simulating winter eutrophication water, their growth, physiological property and enzymatic activities were studied, as well as their ecological effects on water body. The results show that M. spicatum grew well and the others had the little freezing injury in the late process of the experiment. The four plants had remarkable effects on removing COD and BOD5 from the eutrophication water. The removal rates of COD and BOD5 were 79.86%, 77.50%, 75.58%, 72.56% and 77.40%, 76.41%, 78.23%, 73.45%, respectively, by M. spicatum, H. vulgaris, J. repens and N. peltatum until the 20th day; and the turbidity of the eutrophication water was decreased gradually during the 20-days cultivation period. Meanwhile, the removal rates for TN and TP were 80.39%, 46.45%, 48.01%, 45.59% and 69.80%, 52.12%, 50.85%, 34.29%, respectively, by the four plants till the end of the experiment. The concentrations of COD, BOD5 and the turbidity of the eutrophication water increased slightly after cultivating other three plants for 25 days except for M. spicatum. Chla and Chlb contents of the four plants increased significantly in the early period, but the Chla/b content had little difference among the treatments before and after the experiment compared with the control. Moreover, soluble protein contents increased remarkably and MDA contents decreased. CAT, POD and SOD activities of the four plants cultivated in the eutrophication water increased significantly compared with those before the experiment. With the water quality improving, most of physiological and biochemical indexes of the four plants were closed to the steady level before the experiment. It was indicated that eutrophication water was beneficial to the growth of aquatic plants and increased their resistance.